Efficacy of Low-Level Laser Therapy in Wound Healing and Pain Reduction After Gingivectomy: A Systematic Review and Meta-analysis: Wound healing and pain reduction by low-level laser therapy after gingivectomy - Abesi, Farida; Derikvand, Nahid (Journal of Lasers in Medical Sciences, 2023)
Introduction: Complete healing of a gingivectomy wound usually takes between one and two months. To speed up this process, different topical medications have been reported. In addition, there are different studies assessing the efficacy of low-level laser therapy (LLLT) in terms of wound healing and pain relief subsequent to gingivectomy, yielding inconsistent outcomes. In the present study, we systematically reviewed the existing evidence in the literature to resolve the given conflicts. Methods: We searched for the studies published from inception to 1 April 2023 in Embase, PubMed, and Scopus databases without language limitation by the use of appropriate keywords. We included randomized or non-randomized clinical trial studies that appraised the efficacy of LLLT in pain reduction and wound healing in adult patients who underwent gingivectomy. We pooled the continuous data concerning the pain visual analog scale and the healing index extracted from the individual studies to provide a standardized mean difference (SMD) with a 95% confidence interval (CI), using a random-effects model. Results: Out of 188 sources initially captured from the database search, six studies were ultimately included. Regarding wound healing, the LLLT group exhibited a significantly higher mean value of the healing index compared to the control group on days 3 (SMD, 0.93; 95% CI, 0.39 to 1.47) and 7 (SMD, 1.03; 95% CI, 0.49 to 1.57) post-surgery. Also, significant differences were noted in the postoperative pain reduction between the two groups on days 3 (SMD, -2.00; 95% CI, -2.48 to -1.51) and 7 (SMD, -2.44; 95% CI, -4.66 to -0.22) post-surgery. Conclusion: According to the present systematic review, LLLT could potentially be an efficient adjunctive treatment after gingivectomy for wound healing acceleration and patient pain alleviation.